RELATIONSHIP BETWEEN PERSONAL SELF-EFFICACY AND FLOOD DISASTER PREPAREDNESS OF INDONESIAN NURSES - Wurjatmiko, Adi Try; Zuhriyah, Lilik; Fathoni, Mukhamad (Public Health of Indonesia, 2018)
Background: Indonesia is one of the countries that is prone to natural disaster. There are between 1,500-2,000 cases of natural disasters annually and most of the cases are related to hydro meteorological activities such as flood. Preparedness is a critical phase in disaster management as it is able to decrease or prevent negative effects of natural disasters for example negative effects of natural disaster in health sector. Nurse preparedness is one of the determining factors in describing how severe effects of natural disasters are in health sector.Objective: To identify and analyze relationship between personal self-efficacy and flood disaster preparedness of Indonesian nurses.Method: The study used analytical observational design with cross sectional approach. The population was 191 nurses and the samples were 160 nurses working in public health centers. The sampling method was purposive sampling. The setting on the study was 5 public health services located in areas prone to flood in Kendari, Southeast Sulawesi, Indonesia. Spearman rank correlational test was used for data analysis with significant level (Î±) =0.05.Results: Spearman Rank correlational test showed a significant relationship between self-efficacy and flood disaster preparedness of nurses (p =0.00 and r =0.63).Conclusion: Personal factor such as nurses' self-efficacy in dealing with flood is related to their flood disaster preparedness in Kendari, Southeast Sulawesi, Indonesia.